Use of sesame by-product and optimized extrusion to obtain a functional flour with improved techno-functional, nutritional and antioxidant properties - Ruiz Armenta, Xóchitl Ariadna; Ruiz Armenta, Jefte Esaú; Espinoza Moreno, Ramona Julieta; Gutiérrez Dorado, Roberto; Aguilar Palazuelos, Ernesto; Zazueta Morales, José de Jesús; Gómez Favela, Mario Armando (Acta Universitaria, 2022)
Sesame is used mainly to obtain oil, generating a sesame by-product cake that is rich in protein, dietary fiber, and phytochemicals. Extrusion is an efficient technology to obtain functional foods. The aim of this work was to optimize the extrusion process to find the best combination of extrusion temperature (ET)/screw speed (SS) in order to produce optimized extruded sesame by-product flour (OESBF), with high values of water absorption index (WAI), water solubility index (WSI), in vitro protein digestibility (IVPD), total phenolic compounds (TPC), and antioxidant activity (AoxA). A rotatable composite central experimental design with two factors and five levels was applied. Desirability function was used to optimize the extrusion process variables. The best combination of extrusion process variables was ET = 139 °C/80 rpm. The OESBF showed higher values of evaluated responses than unprocessed sesame by-product flour, suggesting that OESBF could be used in beverages, porridges, and deserts.